2018
DOI: 10.1021/acsomega.8b01871
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide–Chitosan Composite Material for Treatment of a Model Dye Effluent

Abstract: Graphene oxide (GO) was cross-linked with chitosan to yield a composite (GO-LCTS) with variable morphology, enhanced surface area, and notably high methylene blue (MB) adsorption capacity. The materials were structurally characterized using thermogravimetric analysis and spectroscopic methods (X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, and 13 C solid-state NMR) to support that cross-linking occurs between the amine groups of chitosan and the −COOH gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 48 publications
6
54
0
Order By: Relevance
“…Chitosan represents an alternative as ecofriendly complexing agent because of its low cost, its intrinsic characteristics, e.g., renewable, nontoxic and biodegradable resource, and hydrophilicity, and its chemical properties, e.g., polyelectrolyte at acidic pH, high reactivity, coagulation, flocculation and biosorption properties, resulting from the presence of reactive hydroxyl and mostly amine groups in the macromolecular chains (Roberts 1992;Sandford 1989;Skjåk-Braek et al 1989;de Alvarenga 2011;Teng 2016). These groups allow chemical modifications yielding different derivatives for specific domains of application (Bhatnagar and Sillanpää 2009;Sudha 2011;Azarova et al 2016;Arfin 2017;Ahmed and Ikram 2017;Sudha et al 2017;Wang and Zhuang 2017).…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan represents an alternative as ecofriendly complexing agent because of its low cost, its intrinsic characteristics, e.g., renewable, nontoxic and biodegradable resource, and hydrophilicity, and its chemical properties, e.g., polyelectrolyte at acidic pH, high reactivity, coagulation, flocculation and biosorption properties, resulting from the presence of reactive hydroxyl and mostly amine groups in the macromolecular chains (Roberts 1992;Sandford 1989;Skjåk-Braek et al 1989;de Alvarenga 2011;Teng 2016). These groups allow chemical modifications yielding different derivatives for specific domains of application (Bhatnagar and Sillanpää 2009;Sudha 2011;Azarova et al 2016;Arfin 2017;Ahmed and Ikram 2017;Sudha et al 2017;Wang and Zhuang 2017).…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…One of the most important properties of chitosan is its cationic nature. This aminopolysaccharide is the only natural cationic polymer in the nature (Roberts 1992;Kurita 1998Kurita , 2006Ujang et al 2011;Teng 2016). At low pH, usually less than about 6.3, chitosan's amine groups are protonated conferring polycationic behavior to polymer while at higher pH (above 6.3), chitosan's amine groups are deprotonated and reactive.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…A second minor weight loss observed for all materials ranged from 120 to 180 • C due to desorption of vapors from the hardening agent [62]. In aprevious study, it was reported that GO begins to decompose/deteriorate at a variety of elevated temperatures of 120 • C [63], 150 • C [51] and 200 • C [20], which leads to the loss of its surface-bound oxygen functional groups. The TGA for GO composites did not have a significant weight loss compared to the pure epoxy, possibly due to the small GO loadings.…”
Section: Thermal Gravimetric Analysismentioning
confidence: 96%
“…And the adsorption followed a PSO kinetics and Freundlich-type multilayered model. Recently, Sabzevari et al [123] pointed out that current GO framework products were of limited applications in water treatment because of scalability as the result of repulsive hydration forces between GO layers. To this end, they tried to cross-link GO within chitosan to yield a composite (GO-LCTS) via the interaction between the amine groups of chitosan and the carboxyl groups of GO, resulting in enhanced surface area and structural stability.…”
Section: Graphene Oxide (Go) Based Composite Materials For Water Rmentioning
confidence: 99%